2011
DOI: 10.1007/s12070-011-0352-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Audio Vestibular Profile of Meniere’s Disease in a Tertiary Care Centre in India

Abstract: The aims of this study are to determine the frequency of patients presenting with Meniere's Disease(MD) in an Indian setting, using the American Academy of Otolaryngology-Head and Neck Surgery (AAO) diagnostic criteria, and to describe the clinical and audio vestibular profiles of these patients. The study was based on prospective case series design in the settings of a tertiary referral hospital. The study included all consecutive patients aged between 5 and 75 years presenting with the history of hearing los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Our finding was the same. Moreover, the audiological, eye movement, and bithermal caloric test findings of the patients were similar to the literature [19,35,[37][38][39][45][46][47][48][49][50][51][52] . Head-shaking nystagmus has been reported as 60% previously, though the value was 20.4% in this study [38] .…”
Section: Discussionsupporting
confidence: 87%
“…Our finding was the same. Moreover, the audiological, eye movement, and bithermal caloric test findings of the patients were similar to the literature [19,35,[37][38][39][45][46][47][48][49][50][51][52] . Head-shaking nystagmus has been reported as 60% previously, though the value was 20.4% in this study [38] .…”
Section: Discussionsupporting
confidence: 87%
“…It has been suggested that extended high frequency audiometry (HFA) testing might reveal cochlear damage at higher frequencies than investigated by a conventional audiogram (Yildirim et al, 2010 ; Mehrparvar et al, 2011 ). Concerning the application of HFA in young people exposed to recreational noise, only limited research has been performed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Meniere's disease was diagnosed in 39 patients (29.77%) with ENG trinary code of ''1101'', ''0111'', ''2000'', ''0101'', ''0001'', ''2011'', ''0100'', ''2021'', ''1120'', ''2111'' and ''2100''. All the patient diagnosed as Meniere's disease were subjected to Electro Cochleo-graphy (EcochG) and the SP/AP ratio were elevated ([ 0.5) in all the patients in the ear showing unilateral/bilateral cold hypo response or unilateral/bilateral warm cold dissociation in bithermal caloric parameter in ENG [15,20]. Right canal paresis was observed in 10 patients (7.63%) with ENG pattern ''1000'', ''1100'' and ''1120''.…”
Section: Observations and Resultsmentioning
confidence: 99%